2018
DOI: 10.1017/s1366728918000895
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit aptitude effects on second language speech learning: Scrutinizing segmental and suprasegmental sensitivity and performance via behavioural and neurophysiological measures

Abstract: The current study examines the role of cognitive and perceptual individual differences (i.e., aptitude) in second language (L2) pronunciation learning, when L2 learners' varied experience background is controlled for. A total of 48 Chinese learners of English in the UK were assessed for their sensitivity to segmental and suprasegmental aspects of speech on explicit and implicit modes via behavioural (language/music aptitude tests) and neurophysiological (electroencephalography) measures. Subsequently, the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 76 publications
(129 reference statements)
5
41
0
Order By: Relevance
“…We find that individuals who encode the neural representation of the second formant of speech more robustly are also better able to perceive English vowels. This is in accordance with previous findings that vowel perception is linked to the extent to which the frequency-following response distinguishes between different vowels (Won et al, 2016), and that formant encoding in the frequency-following response tracks with the accuracy of segmental L2 production (Saito et al, 2018). Here we extend these results by showing that neural formant encoding and behavioural measurements of spectral processing explain independent variance in speech perception.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We find that individuals who encode the neural representation of the second formant of speech more robustly are also better able to perceive English vowels. This is in accordance with previous findings that vowel perception is linked to the extent to which the frequency-following response distinguishes between different vowels (Won et al, 2016), and that formant encoding in the frequency-following response tracks with the accuracy of segmental L2 production (Saito et al, 2018). Here we extend these results by showing that neural formant encoding and behavioural measurements of spectral processing explain independent variance in speech perception.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a link between rhythm perception and production and second language acquisition is in line with our precursor research which demonstrated that adult second language learners with greater rhythmic sensitivity spoke more fluently (with faster speech rate and fewer pauses and repetitions) (Saito et al, 2018). This relationship between rhythm perception and second language learning may help explain prior findings of links between musical training and second language learning success (Slevc & Miyake, 2006;Martinez-Montes et al, 2013;Swaminathan & Gopinath, 2013;Cooper, Wang, & Ashley, 2017;Dittinger, D'Imperio, & Besson, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although the study found that the two explicit aptitude factors explained approximately 10% of variance in the participants’ L2 pronunciation attainment, it would be intriguing to replicate the findings by adopting a more comprehensive set of aptitude measures that are designed to tap into explicit and implicit learning abilities (with and without awareness), and domain-specific and domain-general abilities (associated with language learning and applicable to any general skill acquisition) in both the receptive and the productive modes (cf. Saito, Sun, & Tierney, 2018, for explicit and implicit sensitivity to segmental and suprasegmental sensitivity)…”
Section: Discussionmentioning
confidence: 99%